Suicidal ideation among outpatients with depression in mental hospital in Kabul Afghanistan / Mahjabin Shahid - Shahid, Mahjabin (2018)
Introduction: Depression is a serious and common medical illness that affects the way of one’s feeling, thinking and acting, negatively, and lead to a persistent feeling of sadness and losses of interest in activities once enjoyed as defined by American Psychiatric Association (APA, 2016). Depression could lead to a variety of physical and emotional problems and can decrease a person's ability to function at work and home (Parekh, 2017). Globally, depression is found to be the second-leading cause of disability with slightly more than 4 percent of the world's population diagnosed with (Dewey, 2013). Methodology: A quantitative cross-sectional design was conducted. The study involves 143 samples from outpatients with depression in mental hospitals of Kabul-Afghanistan. The severity of depression was assessed by BDI, the level of social support was assessed by MDSS, the level of suicidal ideation was assessed by BSIS, and the K10 was performed to assess the level of distress. The data collection duration was from 4/10/2017-8/10/2017. Results: The result of the study shows the high level of suicidal ideation 16.00(13.00-16.00) among outpatients with depression in mental hospitals of Kabul-Afghanistan.